Reading scripture to hear God : Kevin Vanhoozer and Henri de Lubac on God's use of scripture in the economy of redemption /: Kevin Vanhoozer and Henri de Lubac on God's use of scripture in the economy of redemption. (2015) - Storer, Kevin
No abstract available